Oxidation behavior of CuAlTa shape memory alloy at high temperatures - Ercan, Ercan; Dagdelen, Fethi (University of Chemical Technology and Metallurgy, 2019)
The isothermal oxidation behavior of Cu-11Al-3Ta (in mass %) high temperature shape memory alloy (HTSMA) was investigated by using the thermogravimetric analysis (TG) method. The alloy was initially heated under standart atmospheric pressure in the range from 25°C to 1000°C with a heating rate 20°C/min. The oxidation gain was linear till 600°C, while parabolical at higher temperatures. Different isothermal oxidation temperatures (700°C, 800°C, 900°C and 1000°C) were chosen in the temperature interval investigated. The oxidation kinetics was followed by the gravimetric method at the temperature values selected. The activation energy of the process was calculated using the Arrhenius relation. The phase transformation temperatures (As, Af, Ms and Mf) of the as-cast alloy were determined by the differential scanning calorimetry (DSC) method. They referred to 291°C, 396°C, 287°C and 224°C, respectively. It was found that they changed significantly in the course of oxidation. Many martensite plates were observed in the alloy's structure using Nikon Eclipse MA200 optical microscope. Grain boundaries were also detected. © 2019, University of Chemical Technology and Metallurgy.
Keywords: Oxidation kinetics; Shape memory alloys; Thermal activation energy